EXPORT OF AGRICULTURAL PRODUCTS IN THE CONDITIONS OF WAR: REGIONAL ASPECTS (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Agriculture is one of the important export-oriented sectors of the economy of Ukraine. In the conditions of constant structural changes in the economy under the influence of economic and political instability, it is expedient to investigate the place of agricultural products in commodity exports of Ukraine, as well as in the formation of the export potential of the regions. It is urgent to identify the regional peculiarities of the export of agricultural products, to determine the specialization of the regions.The purpose of the article. The purpose of the study is to analyze the regional structure of agricultural exports, to determine the place of agriculture in the commodity exports of the regions, to point out the changes in the export structure caused by the full-scale war.Metods. The conducted research was based on the analysis of statistical data on export volumes in Ukraine and in the regions. Conclusions about regional aspects of export of agricultural products are made on the basis of data systematization, scientific abstraction and methods of comparative analysis.Results. The current trends in the export of agricultural products of Ukraine were studied. The share of regions in the formation of commodity exports of agricultural products of Ukraine has been established. The changes in the export structure (in terms of main product groups and subgroups) that took place under the influence of a full-scale war were determined. The share of agricultural products in the formation of the commodity structure of the regions' exports has been determined, and the export specialization of the regions (within agricultural products) has been determined. The main exporters, problems and promising directions of export development in the regions are indicated. It has been established that in certain regions of Ukraine, agricultural export plays a key role in the formation of the region's export potential.Conclusions. Based on the results of the conducted research, conclusions were made about the specialization of regions by types of agricultural products, the peculiarities and changes in trends regarding the export of agricultural products in the regions were indicated.
Keywords: export, agriculture, regions, export potential, export product structure.